Comparison of Meteorological Drought using SPI and SPEI - Shashi Shankar Ojha; Vivekanand Singh; Thendiyath Roshni (Salehan Institute of Higher Education, 2021)
Drought assessment is crucial for effective water resources management in a river basin. Drought frequency has increased worldwide in recent years due to global warming. In this paper, an attempt is made to assess the meteorological drought in the Punpun river basin, India using two globally accepted drought indices namely, Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI). The SPI and SPEI at 1-, 3-, 6-, 9-, and 12-month timescale were obtained to analyze the temporal variability of different drought levels. Correlation analysis of available observed data and gridded data has been carried out and the correlation coefficient was found to be 0.956. Hence gridded rainfall data from the year 1991 to 2020 is used for further analysis. Potential evapotranspiration (PET) used in the calculation of SPEI was computed by the Thornthwaite method. Water deficit was observed throughout as there is a decrease in rainfall and an increase in PET during the selected period. The results show that the period 2004 to 2006 and 2009 to 2010 years are observed as drought periods by both indices for almost all timescale. The intensity and duration of drought have increased after 2004. A negative trend of both the indices have been observed in all seasons on all timescale, which clearly shows a transition from near normal to moderately dry during the selected time period. The highest correlation between both the indices is for the 12-month scale with R² value 0.92 and the RMSE value 0.28. The main outcome of this study is that both SPI and SPEI show a strong correlation on same time scales adopted in this study. The dependency of SPEI on temperature is also observed in this study. Doi: 10.28991/cej-2021-03091783 Full Text: PDF